ANALISA MITIGASI EMISI KARBON SERTA KEEKONOMIAN PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) ATAP ON GRID 463,25 kWp DI PERUSAHAAN FARMASI PADA KAWASAN PT JAKARTA INDUSTRIAL ESTATE PULOGADUNG, JAKARTA TIMUR - Candra Erawan, I Nyoman; Setiawan, I Nyoman; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 10 No 3 (2023): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2023.v10.i03.p4, 2023)
According to the Directorate General of EBTKE, Indonesia has a great deal of untapped potential for PLTS development because the equator passes through the country. Furthermore, the use of PLTS can mitigate the negative effects of carbon emissions caused by conventional power plants' reliance on coal. This research aims to quantify the savings in carbon emissions from PLTS deployment and to conduct an economic analysis of PLTS deployment by considering its Life Cycle Cost (LCC), Levelized Cost of Energy (LCoE), Net Present Value (NPV), and Payback Period (PBP). Profitability Index (PI) and Internal Rate of Return (IRR) for a pharmaceutical firm located in East Jakarta's PT Jakarta Industrial Estate Pulo Gadung. The results of the analysis that has been carried out obtain a total reduction in carbon emissions due to the use of PLTS when compared to JAMALI's electricity carbon emissions of 479.4 tons CO2eq in a year. The use of PLTS affects savings in paying electricity bills of IDR 591,145,354.06 each year and from the economic analysis using the methods (LCC, (LCoE), (NPV), (PBP), (IRR), and (PI) it is obtained that the feasibility The investment in PLTS development in this company is considered feasible.